2020
DOI: 10.1186/s12935-020-01545-9
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines and related signaling pathways in cancer

Abstract: Polyamines are aliphatic compounds with more than two amino groups that play various important roles in human cells. In cancer, polyamine metabolism dysfunction often occurs, and regulatory mechanisms of polyamine. This review summarizes the existing research on the metabolism and transport of polyamines to study the association of oncogenes and related signaling pathways with polyamines in tumor cells. Drugs that regulate enzymes have been developed for cancer treatment, and in the future, more attention shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 94 publications
0
71
0
Order By: Relevance
“…We also found a possible higher potential to produce polyamines mainly due to the increased prevalence of E. coli in the guts of patients with PDAC. Dysregulated polyamine levels have been associated with toxic effects and carcinogenesis, and increased polyamine levels in urine and blood specimens have been found among other cancers, such as skin cancer [ 41 ]. However, we failed to measure polyamines in our subjects, whether there is a relationship between polyamines and PDAC needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a possible higher potential to produce polyamines mainly due to the increased prevalence of E. coli in the guts of patients with PDAC. Dysregulated polyamine levels have been associated with toxic effects and carcinogenesis, and increased polyamine levels in urine and blood specimens have been found among other cancers, such as skin cancer [ 41 ]. However, we failed to measure polyamines in our subjects, whether there is a relationship between polyamines and PDAC needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Several works have demonstrated that PAs have antioxidative effects [10], can promote homology-directed DNA repair [11], and downregulate DNA damage-associated cell death [12,13]. Almost all cells can produce PAs, but their production is especially high in rapidly growing cells; therefore, the concentration of PAs as well as the gene expression and activity of enzymes involved in PA biosynthesis are higher in cancer tissues than in normal surrounding tissues [14][15][16]. Therefore, the pathway of PA metabolism is a promising target for chemotherapy and chemoprevention [17].…”
Section: Introductionmentioning
confidence: 99%
“…We argue that at least 3 strong roles of glutamine exist in prostate and/or prostate cancers. First, the most prominent function of the prostate is to produce and secrete polyamines, especially spermine, a major component of prostatic fluid, which functions to protect sperm DNA for safe fertilization (Affronti et al., 2020; Li et al., 2020). Glutamine can be metabolized to ornithine by two enzymes, glutaminase (GLS) and ornithine amino transferase (OAT), sequentially, and then ornithine is metabolized to polyamines.…”
Section: Discussionmentioning
confidence: 99%